2021
DOI: 10.1002/btm2.10240
|View full text |Cite
|
Sign up to set email alerts
|

Engineering elastic sealants based on gelatin and elastin‐like polypeptides for endovascular anastomosis

Abstract: Cerebrovascular ischemia from intracranial atherosclerosis remains difficult to treat. Although current revascularization procedures, including intraluminal stents and extracranial to intracranial bypass, have shown some benefit, they suffer from peri-and postoperative morbidity. To address these limitations, here we developed a novel approach that involves gluing of arteries and subsequent transmural anastomosis from the healthy donor into the ischemic recipient. This approach required an elastic vascular sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…To demonstrate noncovalent interaction mediated dynamic molecular rearrangements, S-nCAGE 1 hydrogel, with the best mechanical properties (highest ultimate strength, stretchability, toughness, and tensile modulus), underwent cyclic compression test (Figure g), which exhibited an energy loss of ∼20% upon completion of 20 cycles (Figure h). This was comparable with the energy loss of an elastic hydrogel synthesized with elastin like polypeptide (30% energy loss after 10 cycles). Interestingly, the engineered S-nCAGE 1 hydrogel demonstrated lower energy loss as compared to an elastic sealant made of modified recombinant protein, methacryloyl-substituted tropoelastin (MeTro), which was optimized to seal elastic tissues (lungs and blood vessels) in vivo using small and large animal models.…”
Section: Resultssupporting
confidence: 71%
“…To demonstrate noncovalent interaction mediated dynamic molecular rearrangements, S-nCAGE 1 hydrogel, with the best mechanical properties (highest ultimate strength, stretchability, toughness, and tensile modulus), underwent cyclic compression test (Figure g), which exhibited an energy loss of ∼20% upon completion of 20 cycles (Figure h). This was comparable with the energy loss of an elastic hydrogel synthesized with elastin like polypeptide (30% energy loss after 10 cycles). Interestingly, the engineered S-nCAGE 1 hydrogel demonstrated lower energy loss as compared to an elastic sealant made of modified recombinant protein, methacryloyl-substituted tropoelastin (MeTro), which was optimized to seal elastic tissues (lungs and blood vessels) in vivo using small and large animal models.…”
Section: Resultssupporting
confidence: 71%
“…Due to this highly cross-linked structure of elastin, tissues can undergo high deformation [ 91 , 174 , 175 ]. For these reasons, EL-based hydrogels have been posed as a prime biomaterial, with better mechanical properties than most biopolymeric hydrogels and good biocompatibility (>80%), although further research is required to optimize elastin-based hydrogels’ in vivo performance [ 92 , 94 , 95 ]. Unal et al (2021) developed a hybrid GelMA/elastin-based composite hydrogel that showed excellent biodegradation ability in vivo when implanted subcutaneously in a murine animal model, as well as remarkable biocompatibility and mechanical properties with potential for vascular applications, specifically for endovascular anastomosis [ 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bioadhesives and sealants can be classified based on their material makeup, adhesion mechanism, method for adhesion initiation, and biocompatibility. 8,30 Multiple biomedical sealants and hemostatic agents, including TISSEEL ® (fibrin sealant), 31 GelMA/GelMAC, 32,33 BioGlue, [34][35][36] and Gelfoam 37,38 all fit into the category of internal/intrabdominal bioadhesives and have shown clinical efficacy in stopping bleeds and initiating the woundhealing process, but every sealant has its limitations.…”
Section: Discussionmentioning
confidence: 99%